UHPC without shrinkage to micro-expansion deformation

Through the full-scale reduction design scheme, the component proportion and particle size distribution in UHPC are adjusted, and the problem of large self-contraction of UHPC is solved, achieving the effect of no shrinkage to micro-expansion, while maintaining high mechanical properties and green and low-carbon properties.

CN119822719AActive Publication Date: 2025-04-15JIANGSU SOBUTE NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202411909637.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-15
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Currently, ultra-high performance concrete (UHPC) has increased its strength and is large in self-contraction, making it difficult to achieve the effect of no shrinkage or even slightly expansion. When using expansion agents and internal curing materials, expanding cracks and internal defects will be introduced, affecting the strength and fiber toughening effect.

Method used

The full-scale reduction design scheme is adopted, and the cement usage is reduced by adjusting the proportion and particle size distribution of components such as cement, active blends, inert blends, reduced blends, fibers, etc., and the cement usage is reduced. Low-active fly ash and finely ground slag powder are used as active blends, and the inert blends and reduced blends are used to reduce self-shrinkage.

Benefits of technology

It significantly reduces the self-contraction of UHPC, achieves the effect of no shrinkage to slightly expanding, while maintaining high mechanical properties, reducing the amount of cement and using industrial waste slag, and has green and low-carbon properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822719A_ABST
    Figure CN119822719A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly discloses UHPC (Ultra High Performance Concrete) without shrinkage to micro-expansion deformation. The UHPC belongs to a scheme of reducing from a cement-active admixture-inert admixture-aggregate-fiber full scale, the problem of large self-constriction of traditional UHPC is solved, and non-constriction and even micro-expansion of the UHPC can be realized. The 28d compressive strength of the UHPC standard curing is greater than 130MPa, the 28d ultimate flexural tensile strength is greater than 20MPa, the 28d ultimate tensile strength is greater than 8MPa, and both high mechanical property and high volume stability are realized. The use amount of the cement is low, and a large amount of industrial waste residues and regenerated construction waste products are used, so that the brick is more environment-friendly; the method has the advantages of simple process, low cost, no use of silica fume, superfine mineral powder, rice hull ash and other superfine powder in conventional UHPC, reduction of energy consumption and cost, convenience in production and use, great improvement of the construction efficiency, and extremely high large-scale application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular, relates to UHPC with no shrinkage or slight expansion deformation. Background Art

[0002] Since the reaction of cementitious materials such as cement and active admixtures will lead to a decrease in volume, and as the reaction proceeds, the relative humidity inside the matrix decreases, which will also produce a self-drying effect. Therefore, autogenous shrinkage is the main reason for the poor volume stability of cement-based materials.

[0003] For ordinary concrete and high-strength concrete, their autogenous shrinkage is generally 100με~200με and 200με~500με. Low shrinkage or even slight expansion of ordinary concrete can be achieved by using internal curing materials such as zeolite powder, pottery sand, recycled aggregate or various expansion agents. For example, Chinese patents CN 112876157A and CN 111620662A respectively use modified recycled aggregate and zeolite powder to reduce shrinkage, while Chinese patents CN 111978045A and CN 110698145A use expansion agents to achieve slight expansion of ordinary concrete. However, with the increase of strength grade, for high-strength / ultra-high-strength concrete or high-strength / ultra-high-strength grouting materials, due to the reduction of water-cement ratio and the addition of ultra-fine powder, the effect of reducing shrinkage by the above-mentioned single means becomes not obvious, and it is usually necessary to use the two measures of adding internal curing materials and expansion agents in combination, such as Chinese patents CN113429181A, CN 113087483A, CN 112110689A, etc.; or on the basis of one of the measures, further reduce the amount of cement (such as Chinese patents CN 111892342A, CN 115057659A, etc.), add salt gypsum (such as Chinese patents CN114213093A, CN 112358250A, etc.) or introduce active steel slag sand (such as Chinese patent CN 110759678A), copper tailings (such as Chinese patent CN 114956699A), thereby reducing the shrinkage of high-strength / ultra-high-strength concrete or high-strength / ultra-high-strength grouting materials, but because a certain amount of high-activity, high-specific surface energy powder particles are still used, therefore, on the basis of not reducing the mechanical properties, ultra-high-strength concrete and ultra-high-strength grouting materials can only achieve no shrinkage (such as Chinese patents CN 114230278A, CN110759678A, CN 113501695A, etc.).

[0004] However, ultra-high performance concrete (UHPC) has extremely low water-cement ratio, high ultrafine powder dosage, material characteristics of steel fiber, and ultra-high strength and ultra-high toughness mechanical properties. A large amount of highly reactive materials and the rapid decrease of internal relative humidity make its autogenous shrinkage large, generally up to 600με~1000με. Although the use of internal curing materials, expansion agents, reduced cement dosage and their combined use mentioned in the above technology can reduce UHPC autogenous shrinkage to a certain extent, due to its own lower water-cement ratio and more ultrafine and highly reactive powder dosage, UHPC still has a certain amount of autogenous shrinkage when ultra-high strength concrete and ultra-high strength grouting materials can only achieve no shrinkage. Therefore, the current research on UHPC is mainly based on low shrinkage.

[0005] In addition, unlike ordinary concrete, high-strength / ultra-high-strength concrete and high-strength / ultra-high-strength grouting materials, since the ultra-high strength of UHPC comes from its dense microstructure, the addition of more expansion agents and internal curing agents can significantly reduce shrinkage, but the resulting expansion cracks and internal defects will have an adverse effect on the strength and fiber toughening effect. Therefore, the shrinkage reduction effect of expansion agents and internal curing agents on UHPC is limited. For materials such as salt gypsum, active steel slag sand, and copper tailings, due to their high content of corrosive ions such as chloride ions and the risk of heavy metal pollution, they will have a negative impact on the internal steel fiber corrosion and environmental safety, so they are not suitable for use in UHPC. Although some studies have mentioned that active steel slag sand contains fCaO and fMgO, which can act as expansion agents to prepare a non-shrinkage sprayable ultra-high performance concrete, the relevant shrinkage data is not mentioned therein; and the microsilica fume and slag powder used therein are still nano-silica fume and ultra-fine mineral powder, which have extremely high reactivity and extremely high specific surface area, so the shrinkage risk is still very large.

[0006] By comparing and analyzing the research on UHPC shrinkage reduction technology, it is found that current measures are mostly concentrated on single or several limitations such as internal curing agents (organic, inorganic porous / water-absorbing materials), expansion agents (calcium aluminate, calcium oxide, magnesium oxide, etc.), and appropriate reduction of cement dosage. However, the problem of large autogenous shrinkage cannot be completely overcome. Therefore, current research on UHPC still cannot achieve the effect of no shrinkage or even slight expansion, and continuous improvement research is still needed. Summary of the invention

[0007] At present, the shrinkage reduction technology of UHPC only stays at a single or several limited levels, and less attention is paid to another key factor affecting autogenous shrinkage - a large amount of highly active and high surface energy admixtures. The use of silica fume and ultrafine mineral powder will inevitably lead to large autogenous shrinkage. Although there are studies to remove silica fume to avoid this problem, the high activity and high surface energy calcined clay that replaces it will still lead to large autogenous shrinkage. Therefore, in view of the fact that it is currently impossible to completely overcome its large autogenous shrinkage and achieve the problem of no shrinkage or even slight expansion of UHPC, the inventors of the present invention, based on the long-term research on the shrinkage reduction technology of UHPC, proposed a design scheme for shrinkage from cement-active admixture-inert admixture-aggregate-fiber full scale, and developed a new UHPC with no shrinkage to slight expansion deformation. The UHPC with no shrinkage to slight expansion deformation can significantly reduce autogenous shrinkage, and achieve the effect of no shrinkage to slight expansion on the basis of ensuring the mechanical properties of UHPC.

[0008] The present invention specifically adopts the following technical solutions:

[0009] A UHPC with no shrinkage or slight expansion deformation, which is composed of the following components mixed evenly by weight:

[0010] Cement: 300-600 parts;

[0011] Active admixture: 100-300 parts;

[0012] Inert admixture: 120-380 parts;

[0013] Shrinkage-reducing admixture: 60 to 250 parts;

[0014] Active stimulant: 20-120 parts;

[0015] Sand: 900-1200 parts;

[0016] Coarse aggregate: 0-500 parts;

[0017] Fiber: 100-250 parts;

[0018] Compensation agent: 5-25 parts;

[0019] Water reducing agent: 7-25 parts;

[0020] Water: 70-220 parts.

[0021] The active admixture is a mixture of fly ash and ground slag powder, and the mass of the ground slag powder accounts for 0-50% of the mass of the active admixture. That is, the active admixture is either pure fly ash or a mixture of no more than half (including half) of ground slag powder and fly ash. The average particle size of fly ash and ground slag powder is 5μm-20μm.

[0022] Furthermore, in the active admixture, the powder particles with an average particle size of 5 μm to 10 μm account for 50% to 80% of the mass of the active admixture. That is, the active admixture is a mixture of 50 wt% to 80 wt% of small-particle powder and the remaining 20 wt% to 50 wt% of large-particle powder, the average particle size of the small-particle powder is 5 μm to 10 μm, and the average particle size of the large-particle powder is 10 μm (not included) to 20 μm.

[0023] The inert admixture is any one of limestone powder and quartz powder, or a mixture of the two in any proportion, and the average particle size of the limestone powder and the quartz powder is 3 μm to 20 μm.

[0024] Furthermore, in the inert admixture, the powder particles with an average particle size of 3 μm to 10 μm account for 50% to 100% of the mass of the inert admixture. That is, the inert admixture is either pure small-particle powder, or a mixture of large-particle powder and small-particle powder not exceeding half (including half), the average particle size of the small-particle powder is 3 μm to 10 μm, and the average particle size of the large-particle powder is 10 μm (excluding) to 20 μm.

[0025] The shrinkage reducing admixture is any one of zeolite powder, ceramic powder and kaolin, or a mixture of at least two of them in any proportion, and the average particle sizes of the zeolite powder, ceramic powder and kaolin are all 3 μm to 20 μm.

[0026] Furthermore, in the shrinkage-reducing admixture, the powder particles with an average particle size of 3 μm to 10 μm account for 50% to 100% of the mass of the shrinkage-reducing admixture. That is, the shrinkage-reducing admixture is either pure small-particle powder, or a mixture of large-particle powder and small-particle powder not exceeding half (including half), the average particle size of the small-particle powder is 3 μm to 10 μm, and the average particle size of the large-particle powder is 10 μm (excluding) to 20 μm.

[0027] The active activator is any one of anhydrite, hemihydrate gypsum and dihydrate gypsum, or a mixture of at least two of them in any proportion, and the average particle sizes of anhydrite, hemihydrate gypsum and dihydrate gypsum are all 5 μm to 30 μm.

[0028] The sand is a mixture of porous sand and hard sand, and the mass of the porous sand accounts for 10% to 20% of the mass of the sand. That is, the sand is a mixture of 10wt% to 20wt% of porous sand and the remaining 80wt% to 90wt% of hard sand.

[0029] Furthermore, the porous sand is selected from any one of pottery sand, coral sand, recycled aggregate sand, or a mixture of at least two of them in any proportion; the hard sand is selected from any one of river sand and quartz sand, or a mixture of the two in any proportion.

[0030] Generally, the maximum particle size of sand does not exceed 2.36 mm.

[0031] Generally, ordinary Portland cement and / or Portland cement with a strength grade of 42.5 or above can be selected as cement.

[0032] Generally, the coarse aggregate is selected from any one of basalt, limestone, granite, or a mixture of at least two of them in any proportion, and the particle size of the coarse aggregate is 5 mm to 16 mm.

[0033] Generally, the fiber has a diameter of 0.15 mm to 0.4 mm and a length of 13 mm to 25 mm; and the shape is selected from any one of straight, hooked or wavy copper-plated steel fibers, or a mixture of at least two in any proportion.

[0034] Generally, the compensating agent is selected from any one of calcium oxide, magnesium oxide, calcium oxide-magnesium oxide composite, or a mixture of at least two of them in any proportion.

[0035] Generally, the water reducing agent is a polycarboxylic acid high efficiency water reducing agent, and the water reducing rate is not less than 30%.

[0036] The UHPC with no shrinkage to slight expansion deformation provided by the present invention is designed with the full-scale reduction of cement-active admixture-inert admixture-aggregate-fiber as the design concept, specifically:

[0037] First, since the theoretical final hydration degree of cement in UHPC is only 30% to 60%, and the actual hydration degree is even lower, the maximum proportion of cement usage in cementitious materials is reduced to less than 70% in the present invention (the cement usage in conventional UHPC usually accounts for more than 70% of cementitious materials), thereby significantly reducing the amount of cement usage to reduce the largest source of autogenous shrinkage, namely, the autogenous shrinkage caused by cement hydration.

[0038] Second, the present invention only uses fly ash and ordinary mineral powder (i.e., ground slag powder) with relatively low activity and small surface energy as the source of active admixtures to reduce the self-shrinkage caused by the active admixtures; in contrast, silica fume, ultrafine mineral powder, rice husk ash and other cementitious materials with extremely high activity and large surface energy will not only increase the volume shrinkage caused by chemical reactions, but also adsorb a large amount of free water, causing the internal relative humidity to drop rapidly, increasing the pore negative pressure, and further increasing the self-shrinkage.

[0039] Third, due to the low reaction degree of active admixtures, a large amount of active admixtures do not participate in the reaction and only play a filling role. However, the remaining unreacted active admixtures will still affect the autogenous shrinkage. Specifically, the more unreacted active admixtures remain, the higher the concentration of active components in the early reaction, which will increase and accelerate the development of early autogenous shrinkage. Moreover, if the external environment changes in the later stage and the humidity inside the UHPC increases, the remaining unreacted active admixtures will still react and increase the autogenous shrinkage in the later stage. Therefore, a large amount of inactive inert admixtures and microporous shrinkage-reducing admixtures are used to reduce the autogenous shrinkage caused by the reaction and reduce the later shrinkage through internal curing. The low reaction degree of active admixtures also makes it possible to use a large amount of inert admixtures and shrinkage-reducing admixtures. In addition, the inert admixtures and shrinkage-reducing admixtures are mixtures of different gradations. By exerting a tight stacking effect, the negative impact of removing materials such as silica fume and ultrafine mineral powder on the mechanical properties can be reduced. The filler dilution effect of the inert admixtures and the internal curing effect of the shrinkage-reducing admixtures will increase the reaction degree of the cementitious materials in UHPC and improve the mechanical properties.

[0040] Fourth, since fly ash and ordinary mineral powder have low activity, active activators are used to increase their reaction degree, and they can promote the formation of calcium aluminate to reduce autogenous shrinkage. The alkaline environment brought by the dissolution of active activators, the increase in calcium ion and sulfate ion concentrations, can rely on alkali and sulfate to stimulate the activity of fly ash and ordinary mineral powder, and the alkaline environment can destroy the surface structure of slag powder (Si-O-Si, Al-O-Al, Si-O-Al and other covalent bonds), further releasing the internal Ca 2+ 、Al 3+ 、SiO4 4- Plasma; in the high calcium system, the hydration product of alkaline cementitious materials is usually CASH, which has a higher elastic modulus than CSH, thereby improving the mechanical properties of UHPC.

[0041] Fifth, the sand of the present invention is limited to a mixture of porous sand and hard sand. Compared with general organic internal curing materials, porous sand has higher strength. Mixing it with hard sand can not only ensure the mechanical properties, but also reduce shrinkage through internal curing effect.

[0042] Sixth, fibers can exert bridging constraint capabilities and inhibit self-shrinkage while acting as reinforcements.

[0043] Seventh, the UHPC with no shrinkage to slight expansion deformation provided by the present invention can greatly reduce the UHPC self-shrinkage from the perspective of reducing and inhibiting shrinkage, and reach a state close to no shrinkage, based on the combined effects of the above six aspects; and on this basis, the expansion effect of the compensating agent can be used to achieve the no shrinkage and slight expansion effect of UHPC. At the same time, due to the removal of nanoparticles such as silica fume, the density of the UHPC matrix in the present invention is reduced, but the higher modulus CASH, the more reactive active admixtures, and the later internal curing effect can ensure the mechanical properties. Therefore, under the appropriate amount of compensating agent, its good expansion effect will not produce microcracks and thus damage the inside of the matrix.

[0044] Compared with the prior art, the beneficial effects of the present invention are:

[0045] (1) The present invention is based on the all-round shrinkage reduction design concept of cement-active admixture-inert admixture-aggregate-fiber, which solves the problem of large autogenous shrinkage of traditional UHPC and can achieve zero shrinkage or even slight expansion of UHPC.

[0046] (2) The standard curing 28d compressive strength of the UHPC without shrinkage to slight expansion deformation of the present invention is greater than 130MPa, the 28d ultimate flexural tensile strength is greater than 20MPa, and the 28d ultimate tensile strength is greater than 8MPa, achieving a balance between high mechanical properties and high volume stability. Compared with the current UHPC, although a large amount of highly active ultrafine powder (such as silica fume, ultrafine mineral powder, rice husk ash, etc.) is beneficial to mechanical properties, it will also increase autogenous shrinkage, and the addition of expansion agents or internal curing materials will reduce autogenous shrinkage but is also detrimental to mechanical properties. The contradiction between the two has been overcome.

[0047] (3) The UHPC with no shrinkage or slight expansion deformation of the present invention has a low proportion of cement and uses a large amount of industrial waste slag and recycled construction waste products, has excellent green and low-carbon performance, and meets the corresponding environmental protection requirements.

[0048] (4) The UHPC with no shrinkage or slight expansion deformation of the present invention does not need to use high-activity ultrafine powders (generally with a particle size of less than 3 μm) such as silica ash, ultrafine mineral powder, and rice husk ash in conventional UHPC. This can not only reduce the energy consumption and cost in the production, transportation, and packaging of ultrafine powders, but also facilitate the production and use of UHPC, greatly improve the construction efficiency, and has extremely high large-scale application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is the autogenous shrinkage value-time curve of UHPC with no shrinkage to slight expansion deformation in Examples 1 to 5 of the present invention;

[0050] Figure 2is the autogenous shrinkage value-time curve of UHPC with no shrinkage to slight expansion deformation in Examples 6 to 10 of the present invention;

[0051] Figure 3 It is a comparison diagram of the autogenous shrinkage rate-time curves of the UHPC without shrinkage to micro-expansion deformation in Example 3 of the present invention and the comparative UHPC in Comparative Example 1, and the UHPC without shrinkage to micro-expansion deformation in Example 6 and the comparative UHPC in Comparative Example 2;

[0052] Figure 4 It is a comparison chart of the autogenous shrinkage rate-time curve of the UHPC without shrinkage to slight expansion deformation in Example 1 of the present invention and the comparative UHPC in Comparative Examples 3 to 7;

[0053] Figure 5 It is a comparison chart of the autogenous shrinkage rate-time curves of the UHPC without shrinkage to slight expansion deformation in Example 1 of the present invention and the comparative UHPC in Comparative Examples 8 to 12;

[0054] Figure 6 It is a comparison chart of the autogenous shrinkage rate-time curves of the UHPC without shrinkage to slight expansion deformation in Example 4 of the present invention and the comparative UHPC in Comparative Examples 13 to 16. DETAILED DESCRIPTION

[0055] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention may be implemented in many different forms, and the present invention should not be construed as being limited to the specific embodiments set forth herein. On the contrary, these embodiments are provided to explain the principles of the present invention and their practical applications, so that other persons skilled in the art can understand various embodiments of the present invention and various modifications suitable for specific intended applications.

[0056] In order to verify the excellent performance of the UHPC with no shrinkage to slight expansion deformation of the present invention, Examples 1 to 11 and Comparative Examples 1 to 16 including two UHPC systems with and without coarse aggregate are provided.

[0057] The raw materials for preparing UHPC without shrinkage to slight expansion deformation in Examples 1 to 11 and the raw materials for preparing comparative UHPC in Comparative Examples 1 to 16 are as follows:

[0058] The cement is Helin PO 42.5 cement; the fly ash has two types of average particle size of 8 μm and average particle size of 16 μm; the ground slag powder (i.e., mineral powder referred to as mineral powder in Table 2 below) has two types of average particle size of 8 μm and average particle size of 16 μm; the inert admixture is limestone powder and quartz powder mixed in a mass ratio of 1:1, and the mixture has two types of average particle size of 5 μm and average particle size of 14 μm; the shrinkage reducing admixture is zeolite powder, ceramic powder, and kaolin mixed in a mass ratio of 1:1:1, and the mixture has two types of average particle size of 5 μm and average particle size of 14 μm; the active activator is anhydrite, hemihydrate gypsum, and dihydrate gypsum with an average particle size of 20 μm mixed in a mass ratio of 1:1:1; the average particle size of silica fume is 0.8 μm; the average particle size of the ultrafine mineral powder is 2.5 μm. The diameter is 4.5μm; the average particle size of rice husk ash is 8μm; the porous sand is any selection of coral sand, pottery sand, and recycled aggregate sand with a maximum particle size not exceeding 2.36mm (except Example 11); the hard sand is river sand with a maximum particle size not exceeding 2.36mm; the average particle size of the organic internal curing agent (super absorbent resin, SAP) is 130μm, and the water absorption is 10 times the mass of SAP; the coarse aggregate is limestone coarse aggregate with a particle size of 5mm to 16mm; the fiber is a hook-type copper-plated steel fiber with a diameter of 0.2mm and a length of 13mm; the compensator is a calcium oxide-magnesium oxide composite compensator produced by Jiangsu Subote; the water reducer is a polycarboxylic acid high-performance water reducer produced by Jiangsu Subote, and the water reduction rate is not less than 30%.

[0059] The components and their weight fractions in the UHPC provided by Examples 1 to 11 and Comparative Examples 1 to 16 are shown in Table 1 below.

[0060] Table 1 Components and their weight percentages of Examples 1 to 11 and Comparative Examples 1 to 16

[0061]

[0062]

[0063] The material and particle size composition of the active admixture, the particle size composition of the inert admixture, the particle size composition of the shrinkage reducing admixture and the material composition of the sand in Examples 1 to 11 and Comparative Examples 1 to 16 are shown in Table 2 below.

[0064] Table 2 Material composition and weight ratio of active admixture, inert admixture, shrinkage reducing admixture and sand in Examples 1 to 11 and Comparative Examples 1 to 16

[0065]

[0066]

[0067] Performance Testing

[0068] The mixing time is counted from the time when water and water reducing agent are added, and the time when the ultra-high performance concrete mixture with no shrinkage to slight expansion deformation forms a homogeneous slurry is taken as the mixing time; the ultra-high performance concrete with no shrinkage to slight expansion deformation after mixing is tested for fluidity, and the test method refers to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures"; after the fluidity test is completed, the compressive strength specimens (size 100mm×100mm×100m), flexural tensile strength specimens (size 100mm×100mm×400m) and axial tensile strength specimens (dog bone section size 50mm×100mm) are formed, and cured for 28 days under standard conditions, and mechanical properties are tested in accordance with T / CBMF 37-2018 "Basic Properties and Test Methods of Ultra-High Performance Concrete". At the same time, a cylindrical specimen with a diameter of 100mm and a height of 400mm is formed, and the autogenous shrinkage of the ultra-high performance concrete with no shrinkage to slight expansion deformation is tested by the PVC pipe method with the final setting time as the starting point. Among them, a positive autogenous shrinkage value indicates shrinkage, and a negative autogenous shrinkage value indicates expansion (unit × 10 -6 or με). The test results are as follows Figure 1 to Figure 6 and as shown in Table 3 below.

[0069] Table 3 Test results of fresh mix performance and mechanical properties of UHPC in Examples 1 to 11 and Comparative Examples 1 to 16

[0070]

[0071]

[0072] Combination Figure 1-2 From the test results in Table 3, it can be seen that the UHPC with no shrinkage to slight expansion deformation of the present invention has a total stirring time of 5min to 8min, a fluidity of 540mm to 780mm, a 28d compressive strength, an ultimate flexural strength, and an ultimate tensile strength of 132.5MPa to 161.4MPa, 20.8MPa to 27.7MPa, and 8.3MPa to 13.5MP, respectively; and the material property of conventional UHPC with large autogenous shrinkage is significantly improved, and its 60d autogenous shrinkage is only -4.47με to 46.05με, so that the deformation performance of the UHPC is no shrinkage to slight expansion.

[0073] Specifically, Example 1 is a relatively balanced benchmark group of components; the formulas of Example 2 and Example 3 are respectively the maximum shrinkage group in the lowest cement dosage (lowest cement dosage + highest admixture dosage + lowest sand / steel fiber dosage + lowest compensator dosage) and the low shrinkage group in the lowest cement dosage (lowest cement dosage + lowest active admixture dosage + highest sand / steel fiber dosage + highest compensator dosage); the formula of Example 4 is a low water-binder ratio of the low shrinkage group in the lowest cement dosage; the formulas of Example 5 and Example 6 are respectively the minimum shrinkage group in the highest cement dosage (highest cement dosage + lowest active admixture dosage + highest sand / steel fiber dosage + highest compensator dosage). The maximum shrinkage group in the maximum cement dosage (maximum cement dosage + maximum active admixture dosage + minimum sand / steel fiber dosage + minimum compensator dosage); the formulas of Examples 7 to 10 are respectively the groups corresponding to the upper limit of the weight ratio of fly ash to mineral powder, the upper limit of the particle size ratio of active admixtures, the upper limit of the particle size ratio of inert admixtures and shrinkage-reducing admixtures, and the upper limit of the porous sand usage; the formula of Example 11 is compared with Example 4, and its porous sand is a mixture of pottery sand, coral sand, and recycled aggregate sand. It can be seen that the UHPC described in the present invention, within the limit range of each component, no matter how the component ratio is adjusted, can achieve the balance of no shrinkage to micro-expansion deformation, good mechanical properties, and good construction performance.

[0074] Compared with the reference group Example 3, no compensating agent was used in Comparative Example 1, and the amount of shrinkage reducing admixture was increased. Figure 3 From the test results in Table 3, it can be seen that the fresh mix performance and mechanical properties of Comparative Example 1 did not show a significant decrease. However, due to the lack of the expansion effect of the compensating agent, even if the inactive shrinkage-reducing admixture with internal curing effect is added, its autogenous shrinkage is still large, and its 60d autogenous shrinkage can reach 143.42με, and the shrinkage-free effect cannot be achieved.

[0075] Compared with the reference group Example 6, the comparative example 2 uses an excessive amount of compensating agent to reduce the amount of cement. Figure 3 As shown in the test results in Table 3, the amount of compensating agent in Comparative Example 2 is relatively high, and its autogenous shrinkage value is -7.58με, showing a micro-expansion effect. However, due to the large amount of water required for the reaction, the workability of the mixture is reduced; and because the expansion of the compensating agent will reduce the fiber-matrix bonding performance, the ultimate flexural tensile strength and ultimate tensile strength are significantly reduced. Compared with Example 6, its 28d ultimate flexural tensile strength is reduced by 46.9%, and its 28d ultimate tensile strength is reduced by 64.4%.

[0076] Compared with the reference group Example 1, Comparative Example 3 uses a small amount of active admixture, and correspondingly reduces the amount of coarse aggregate, increases the amount of inert and shrinkage-reducing admixtures to overcome the adverse effects of a small amount of active admixture. Figure 4As shown in the test results in Table 3, although Comparative Example 3 has a certain micro-expansion effect, due to the lack of active components and less hydration products, it only relies on reducing coarse aggregate, increasing inertia and reducing the amount of admixtures to improve the packing density, and cannot provide good mechanical properties. Its 28d compressive strength is reduced by 20.6% to only 115.1MPa (it can no longer be called UHPC, and the compressive strength of UHPC is usually required to be greater than 120MPa), and its 28d ultimate tensile strength is reduced by 30.6% to only 7.7MPa.

[0077] Compared with the reference group Example 1, Comparative Example 4 uses an excessive amount of active admixtures, and reduces the inert and shrinkage-reducing admixtures to overcome the adverse effects of excessive active admixtures. Figure 4 From the test results in Table 3, it can be seen that in Comparative Example 4, although the fresh mix performance and mechanical properties are good, the shrinkage caused by the chemical reaction increases due to the use of a large amount of active admixtures, and its 60d autogenous shrinkage can reach 110.53με, which still has a certain autogenous shrinkage.

[0078] Compared with the reference group Example 1, a small amount of active stimulant is used in Comparative Example 5, and the amount of active admixture is increased. Figure 4 From the test results in Table 3, it can be seen that although the amount of active admixture is increased in Comparative Example 5, due to the relatively low reactivity of the active admixture itself, without sufficient active activator, the reaction degree and density of the concrete decrease, resulting in reduced mechanical properties, with a 28d compressive strength of <120MPa and a tensile strength of <8MPa.

[0079] Compared with the reference group Example 1, the comparative example 6 uses an excessive amount of active activator and reduces the amount of cement. Figure 4 From the test results in Table 3, it can be seen that comparative example 6 uses more active activators, but because the particle shape of the gypsum particles is poor, it has a retarding effect, which is not conducive to the fresh mix performance, and the total mixing time exceeds 16 minutes; and too much gypsum will produce a large amount of calcium aluminate, resulting in poor stability of the concrete, which is not conducive to mechanical properties. Its 28d compressive strength is less than 120MPa, and the flexural strength and tensile strength are significantly reduced.

[0080] Compared with the reference group Example 1, no porous sand was used in Comparative Example 7. Figure 4 From the test results in Table 3, it can be seen that although Comparative Example 7 has good fresh mix performance and mechanical properties, it lacks the internal curing effect of porous sand, resulting in large autogenous shrinkage, and its 60d autogenous shrinkage can reach 95.26με.

[0081] Compared with the reference group Example 1, the comparative example 8 uses an excessive amount of porous sand. Figure 5As shown in the test results in Table 3, although Comparative Example 8 has a micro-expansion effect, the fresh mix performance and mechanical properties are greatly reduced due to the increase in the amount of low-strength, low-modulus porous sand. The total mixing time is close to 20 minutes, which is basically unusable under actual complex working conditions; and the 28d compressive strength is less than 120MPa, and the flexural tensile strength and tensile strength are significantly reduced.

[0082] Compared with the reference group Example 1, the amount of fly ash used in Comparative Example 9 is reduced, and the amount of ground slag powder used is increased. Figure 5 From the test results in Table 3, it can be seen that the mechanical properties of Comparative Example 9 are higher. Since the amount of ground slag powder with higher activity is increased and the amount of fly ash with spherical ball effect is reduced, its fresh mix performance is poor and its autogenous shrinkage is large.

[0083] Compared with the reference group Example 1, all active admixtures with a size of 5 μm to 10 μm are used in Comparative Example 10. Figure 5 From the test results in Table 3, it can be seen that in Comparative Example 10, since all active admixtures with small particle sizes are used, the reaction activity brought about by the reduction of the particle size and the significant increase in the free water adsorption capacity will increase the chemical autogenous shrinkage and self-drying shrinkage, and the overall autogenous shrinkage is relatively large.

[0084] Compared with the reference group Example 1, the amount of active admixture in Comparative Example 11 is reduced by 5 μm to 10 μm, and the amount of active admixture is increased by 10 μm to 20 μm. Figure 5 From the test results in Table 3, it can be seen that the reduction in the amount of small-particle active admixtures in Comparative Example 11 is beneficial to reducing shrinkage, but it will lead to a decrease in the overall reaction degree and packing density, thereby deteriorating the mechanical properties.

[0085] Compared with the reference group Example 1, the amount of the inert admixture of 3 μm to 10 μm is reduced in Comparative Example 12, and the amount of the inert admixture of 10 μm to 20 μm is increased. Figure 5 As shown in the test results of Table 3, in Comparative Example 12, due to the reduced amount of small-particle inert admixture, its filling effect on small-scale pores is weakened, the porosity is increased, and the matrix packing density is reduced, which also deteriorates the mechanical properties. In addition, for shrinkage-reducing admixtures, for the same reason as above, reducing the amount of 3μm-10μm particle size particles will also reduce the mechanical properties.

[0086] Compared with the reference group Example 4, Comparative Examples 13 to 15 use part of silica fume, ultrafine mineral powder, and rice husk ash in the active admixture. Figure 6As can be seen from the test results in Table 3, since high-activity ultrafine powders are used in Comparative Examples 13 to 15, their filling effect and ball effect can shorten the stirring time and increase the flow height, but the extremely small particle size will greatly increase the amount of water adsorbed by the particles, causing the internal relative humidity to drop rapidly, thereby increasing the autogenous shrinkage. At the same time, since high-activity ultrafine powders will greatly promote hydration, which is beneficial to mechanical properties, it will greatly increase the autogenous shrinkage, so that the 60d autogenous shrinkage of Comparative Examples 13 to 15 is greater than 140με.

[0087] Compared with the reference group Example 4, Comparative Example 16 uses SAP (organic internal curing agent) instead of porous sand (inorganic internal curing agent). Figure 6 As can be seen from the test results in Table 3, due to the internal curing effect of SAP's own water absorption and expansion and the later water release, its 60d self-shrinkage is -45.2με, showing a slight expansion. However, the large particle size and high water absorption of SAP will greatly increase the stirring time, reduce fluidity, and deteriorate the working performance; and SAP's competitive water absorption is not conducive to the hydration reaction, the large particle size reduces the particle packing density, and its own extremely low strength, so that its mechanical properties are significantly reduced. Compared with Example 4, its 28d compressive strength, ultimate flexural tensile strength and ultimate tensile strength are reduced by 31.3%, 23.7% and 33.7%, respectively.

[0088] It can be seen that the UHPC with no shrinkage to slight expansion deformation of the present invention achieves the full-scale shrinkage reduction effect of low cement dosage, active admixtures with lower activity and coarse and fine particle sizes, inert admixtures with coarse and fine particle sizes, internal curing and shrinkage-reducing admixtures with coarse and fine particle sizes, fine aggregates with internal curing effects, compensating agents with expansion effects, coarse aggregates and fibers that inhibit shrinkage, thereby achieving the ultra-high performance concrete and coarse aggregate ultra-high performance concrete with no shrinkage to slight expansion deformation under the premise of ensuring fresh mix performance and ultra-high mechanical properties. These components influence each other in combination, and do not exist alone.

[0089] It should be noted that, in the above-mentioned embodiment of the present invention, although only one of the options is shown for the convenience of testing, such as the active admixtures are all mixed powders of fly ash and ground slag powder in a mass ratio of 1:1, this is not used to limit all the options of active admixtures. This is because, according to preliminary analysis, for active admixtures, when the ground slag powder is mixed with fly ash at a dosage of no more than 50wt%, the effect of different dosages is equivalent to that of pure fly ash. The same applies to the other components.

[0090] The embodiments used above are only for illustrating and explaining the contents of the present invention, and do not constitute any special limitation to the present invention. Any form of modification made without departing from the basic concept of the present invention, as well as the obvious modifications derived therefrom, shall fall within the protection scope of the present invention.

Claims

1. A UHPC with no shrinkage to slight expansion deformation, characterized in that: It is composed of the following components mixed evenly by weight: Cement: 300-600 parts; Active admixture: 100-300 parts; Inert admixture: 120-380 parts; Shrinkage-reducing admixture: 60 to 250 parts; Active stimulant: 20-120 parts; Sand: 900-1200 parts; Coarse aggregate: 0-500 parts; Fiber: 100-250 parts; Compensation agent: 5-25 parts; Water reducing agent: 7-25 parts; Water: 70-220 parts; The active admixture is a mixture of 50% to 100% fly ash and 0 to 50% ground slag powder, and in the active admixture, the mass proportion of powder particles with an average particle size of 5 μm to 10 μm in the active admixture is 50% to 80%; In the inert admixture, the mass proportion of powder particles with an average particle size of 3 μm to 10 μm in the inert admixture is 50% to 100%; The sand is a mixture of 10wt% to 20wt% porous sand and 80wt% to 90wt% hard sand.

2. The UHPC with no shrinkage to slight expansion deformation according to claim 1, characterized in that: The average particle sizes of the fly ash and the ground slag powder are both 5 μm to 20 μm.

3. The UHPC with no shrinkage to slight expansion deformation according to claim 1, characterized in that: The inert admixture is selected from limestone powder and / or quartz powder, and the average particle size of the limestone powder and the quartz powder is 3 μm to 20 μm.

4. The UHPC with no shrinkage to slight expansion deformation according to claim 1, characterized in that: The shrinkage reducing admixture is selected from at least one of zeolite powder, ceramic powder and kaolin, and the average particle sizes of the zeolite powder, ceramic powder and kaolin are all 3 μm to 20 μm.

5. The UHPC with no shrinkage to slight expansion deformation according to claim 4, characterized in that: In the shrinkage-reducing admixture, the mass proportion of powder particles with an average particle size of 3 μm to 10 μm in the shrinkage-reducing admixture is 50% to 100%.

6. The UHPC with no shrinkage to slight expansion deformation according to claim 1, characterized in that: The active activator is selected from at least one of anhydrite, hemihydrate gypsum and dihydrate gypsum, and the average particle sizes of anhydrite, hemihydrate gypsum and dihydrate gypsum are all 5 μm to 30 μm.

7. The UHPC with no shrinkage to slight expansion deformation according to claim 1, characterized in that: The maximum particle size of the sand does not exceed 2.36 mm.

8. The UHPC with no shrinkage to slight expansion deformation according to claim 7, characterized in that: The porous sand is selected from at least one of pottery sand, coral sand and recycled aggregate sand, and the hard sand is river sand and / or quartz sand.

9. The UHPC with no shrinkage to slight expansion deformation according to any one of claims 1 to 8, characterized in that: The coarse aggregate is selected from at least one of basalt, limestone and granite, and the particle size of the coarse aggregate is 5 mm to 16 mm; The fiber has a diameter of 0.15 mm to 0.4 mm and a length of 13 mm to 25 mm; and the fiber is selected from any one of copper-plated steel fibers having a straight, hooked or wavy shape, or a mixture of at least two of them in any proportion; The compensating agent is selected from at least one of calcium oxide, magnesium oxide, and a calcium oxide-magnesium oxide composite; The water reducing agent is a polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is not less than 30%; The cement is ordinary Portland cement and / or Portland cement with a strength grade of 42.5 or above.

Citation Information

Patent Citations

  • Trapezoidal sleeper square steel micro-expansion concrete

    CN110698145A

  • Quick-hardening early-strength non-shrinkage concrete for freely assembled external wallboard, dry mixing material of concrete, and preparation method and application of dry mixing material

    CN110759678A

  • Concrete doped with modified zeolite

    CN111620662A

  • Preparation method of high-strength low-shrinkage cement composite material

    CN111892342A

  • Micro-expansion concrete and preparation method thereof

    CN111978045A

Cited By

  • UHPC having non-shrinkage to micro-expansion deformation

    WO2026137676A1